How Halal Destination Attribute and Social Media Drive Tourist’s Revisit Intention? - Wenda Wahyu Christiyanto; Nur Ali; Nurianah; Arum Wahyuni Purbohastuti; Rina Suprina; Resa Nurlaela Anwar (Politeknik Negeri Bandung, 2025)
This study examines the influence of halal destination attributes (HDA) and social media marketing (SMM) on tourists’ revisit intention (REV), with trust (TRU) acting as a mediating variable. Set in the context of domestic Muslim tourism, the study examines how travelers’ perceptions of halal-compliant services and their digital engagement shape their behavioral intentions. A quantitative survey was conducted involving 200 domestic tourists who visited halal tourism destinations and relied on social media for recommendations. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings indicate that both HDA and SMM play important roles in building trust, which in turn strengthens tourists’ intention to revisit. The results suggest that trust functions as a key link between destination experience and future travel behavior. Halal-friendly services—such as clear halal certification, prayer facilities, and gender-appropriate amenities—combined with engaging social media content, help build confidence and loyalty among Muslim travelers. This research offers practical implications for destination managers, particularly in Muslim-majority regions. To encourage repeat visits, they must ensure that each touchpoint not only meets halal standards but also effectively communicates value on social media. The study contributes to the growing literature on halal tourism by highlighting trust as a central mechanism that connects destination quality and marketing efforts with sustained tourist engagement.